Sagot :
Answer:
Write a polynomial in each to complete each statement. 7p2 - 7p = 7p.__
Step-by-step explanation:
Step 1. Move the light terms to the left side.
7p2 - 7p = 7p
Step 2. Combine the light terms.
7p2 - 7p - 7p = 0
Step 3. Common factor.
7p2 - 14p = 0
7(p2 - 2p) = 0
Step 4. Divide both sides of the equation by the same term.
7(p2 - 2p = 0
p2 - 2p = 0
Step 5. Use the quadratic formula.
![View image Taekookie3001](https://ph-static.z-dn.net/files/d08/e4d0528151cd58cf2d394f7bf916d6f2.jpg)